Impact of AI Software on Improving Learning Outcomes and Attitudes of Music Students in Chinese Vocational Schools - Ren, Jiuzhou; Edwards, Bosede Iyiade; Jamiat, Nurullizam (Journal of Technical Education and Training, 2024)
This study focused on the application of AI tools in vocational music education. The objective is to determine whether the use of AI tools can help improve music listening and reading skills, thereby helping to address the challenges of access to quality music education by students in poor districts with limited access to learning resources. In a within-subjects experimental procedure involving 44 vocational school students (22 male, 22 female) aged 14-17, participants underwent 3 weeks of learning music listening and reading without technology support (condition 1) and learning with AI support (condition 2). Kimi Assistant AI tool was employed for teaching music listening while Music notation software (Laiyinzhipu) was employed for teaching music reading. Students were tested for both learning and attitude. Three (3) hypotheses were also tested to assess the impact of AI tools on music listening, reading and students’ attitudes. Findings show that using AI software specifically promoted only Melody and Structure indicators in listening skills whereas all the reading skills show marked improvement with AI tool. The implication of this is that AI software might hold more effectiveness regarding the teaching of reading skills. A significant improvement in attitude was also noted with the use of AI tools. However, more in-depth studies are needed to confirm if there are clear correlations between learning outcomes and attitudes with the use of AI software can help students improve their motivation to learn. The study is novel in its focus on music education. The study further shows that a combination of AI software and teacher-led instruction will be more significantly beneficial to students for learning music courses. Recommendations for future studies address the limitations of the study including the short experimental period, software restriction issues, an exploration of learners’ motivation, and studies adopting other designs including surveys and other experimental methods.